2013
DOI: 10.1530/joe-13-0285
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone and Klotho

Abstract: Acromegaly is characterized by excessively high GH and IGF1 levels. Recent data suggest that soluble Klotho (sKlotho) is also elevated in patients with active acromegaly. sKlotho decreases towards normal following removal of the GH-producing pituitary adenoma. The Klotho gene was identified in mice following its accidental disruption by ectopic DNA. It is an ageing suppressor gene of restricted expression (mainly in kidneys, brain, and parathyroid and pituitary glands) encoding a transmembrane protein, mKlotho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 175 publications
(198 reference statements)
3
39
0
1
Order By: Relevance
“…It is suggested that increased mKlotho-proteolytic enzymes activity could lead to decreasing mKlotho and to impaired FGF23 signalling, which explains FGF23 resistance. As a consequence of increased activity of enzymes, sKlotho is increased and contributes to IR [7]. As we observed in our previous study 25(OH)D correlated positively with IGF-1 only in AA group [19].…”
Section: Prace Oryginalnesupporting
confidence: 69%
See 2 more Smart Citations
“…It is suggested that increased mKlotho-proteolytic enzymes activity could lead to decreasing mKlotho and to impaired FGF23 signalling, which explains FGF23 resistance. As a consequence of increased activity of enzymes, sKlotho is increased and contributes to IR [7]. As we observed in our previous study 25(OH)D correlated positively with IGF-1 only in AA group [19].…”
Section: Prace Oryginalnesupporting
confidence: 69%
“…It was shown that Klotho-deficient mice (kl/kl) had a shortened life and a lot of disorders caused by human ageing, including atherosclerosis, osteoporosis, skin atrophy, and pulmonary emphysema [5]. On the other hand, overexpression of Klotho prolongs the lifespan [6,7]. Various functions of Klotho have been described until now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble αKlotho is released through cleavage of the extracellular domain from membrane αKlotho by secretases to function as an endocrine/paracrine substance [26][27][28][29]…”
Section: Klotho-vitamin D-vdr Axismentioning
confidence: 99%
“…The soluble α klotho is characterized by his anti-apoptotic effects especially in DN. Several studies have shown that α klotho expression is decraesed in the renal PCT cells in early stages of DN, in humans and mice model [30,31] Interesting cross talk exist between α klotho-Vitamin D/ Vitamin D receptor-(VDR) axis. Up regulation or restoration of klotho by 1,25(OH)2D3, may provide a mean to slow down the progression of chronic diabetic kidney disease (CDKD).…”
Section: Iron and Oxidative Stressmentioning
confidence: 99%